2007
DOI: 10.1086/510108
|View full text |Cite
|
Sign up to set email alerts
|

The Mercury‐Manganese Binary StarφHerculis: Detection and Properties of the Secondary and Revision of the Elemental Abundances of the Primary

Abstract: Observations of the Mercury-Manganese star φ Her with the Navy Prototype Optical Interferometer (NPOI) conclusively reveal the previously unseen companion in this single-lined binary system. The NPOI data were used to predict a spectral type of A8V for the secondary star φ Her B. This prediction was subsequently confirmed by spectroscopic observations obtained at the Dominion Astrophysical Observatory. φ Her B is rotating at 50 ± 3 km s −1 , in contrast to the 8 km s −1 lines of φ Her A. Recognizing the lines … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 47 publications
3
48
1
Order By: Relevance
“…This linelist includes the Fuhr & Wiese (2006) log g f data for several Fe I and Fe II lines, usually referred to as FW06. The line data and log g f values were updated according to Adelman et al (2006) and Zavala et al (2007), in agreement with our previous abundance works (e.g. Saffe et al 2011).…”
Section: Observational Materialsmentioning
confidence: 87%
See 1 more Smart Citation
“…This linelist includes the Fuhr & Wiese (2006) log g f data for several Fe I and Fe II lines, usually referred to as FW06. The line data and log g f values were updated according to Adelman et al (2006) and Zavala et al (2007), in agreement with our previous abundance works (e.g. Saffe et al 2011).…”
Section: Observational Materialsmentioning
confidence: 87%
“…We caution that the error of the abundances σ presented in these tables correspond to the dispersion 4 http://kurucz.harvard.edu/programs.html of the abundances derived from different lines and do not include the error in the abundances of the Sun, in order to properly compare with previous abundance works (e.g. Zavala et al 2007;Saffe et al 2011). No uncertainty is quoted when only one line is present.…”
Section: Abundance Analysesmentioning
confidence: 98%
“…These anomalies are thought to be produced by radiatively driven diffusion and gravitational settling (Michaud 1970). The observations of Zavala et al (2007) spatially resolve the companion of Her for the first time. The object had previously been known as a single-lined spectroscopic binary with a period of about 560 days (Babcock 1971;Aikman 1976) and an eccentric orbit.…”
Section: Introductionmentioning
confidence: 85%
“…In a recent paper Zavala et al (2007) reported interferometric observations of the mercury-manganese star Her [HD 145389, HR 6023, HIP 79101, J2000:0 ¼ 16 h 08 m 46:18 s , J2000:0 ¼ þ44 56 0 05:7 00 , spectral type B9:p(HgMn), V ¼ 4:22], which is a binary star. This object belongs to a class of peculiar nonmagnetic B-type stars that show abundance anomalies of several elements, some of which (such as Hg and Mn) can be enhanced by orders of magnitude (Preston 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation